Penyuluhan Pembuatan Gummy Candies Daun Kelor untuk Pencegahan Stunting di Desa Slateng Kabupaten Jember - Eryani, Mikhania Christiningtyas; Paramita, Denok Risky Ayu; Aditama, Agnis Pondineka Ria; Handojo, Kukuh Judy (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to increase the knowledge and skills of mothers in Slateng village, Jember, regarding making Moringa Leaves Gummy Candies to prevent stunting in toddlers. The method of implementing this service used interactive counseling. The instrument for evaluating this service was a questionnaire, which was analyzed descriptively, qualitatively, and quantitatively. The results of this service showed that the knowledge and skills of mothers as extension participants increased. It was evidenced by the data before the service process was carried out, the average participant knowledge was 66.25, and after the service was carried out, it became 70.62, so that there was a 4.37% increase in knowledge participants